Capital Account Liberalization and Financial Sector Stability. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper analyzes the linkages between capital account liberalization and other policies influencing financial sector stability. Drawing on country experiences, the paper develops an operational framework for sequencing and coordinating capital account liberalization with other policies aimed at maintaining financial sector stability. Based on the general principles, a methodology for sequencing capital account liberalization is presented in this paper. This methodology, which is illustrated by an example, involves an assessment of capital controls and macroeconomic and financial sector vulnerabilities, and the design of a plan for sequencing capital account liberalization with financial sector reforms and other policies. Financial systems that have been weakened by inappropriate government involvement also face additional risks when operating in international financial markets. The absence of significant macroeconomic imbalances and the high level of official international reserves at the outset of the crisis also appear to be important factors preventing a full-blown exchange crisis. Nevertheless, the prolongation of the crisis lowered economic growth and ultimately led to a recession and increased the total cost of the crisis resolution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet